Korean Herbal Medicine for Treating Henoch-Schonlein Purpura with Yin Deficiency: Five Case Reports - Sung-Kyung Kim; Seung-Seon Ryu; Sunju Park; Sang-Kyun Park; Woo-Jin Choi; Seung-Ho Sun (Korean Pharmacopuncture Institute, 2014)
Objectives: The purpose of this study is to report the clinical effect of Korean medicine (KM) treatment for Henoch-Schonlein purpura (HSP). Methods: Five HSP patients who demonstrated a Yin deficiency and who had a history of a previous upper respiratory tract infection were included in this study. Four patients had arthritis and three had severe stomachache. One of them appeared to have proteinuria and hematuria before starting KM treatment. Results: All patients were improved with only herbal medicine, Jarotang (JRT). Purpura in the lower extremities and abdominal pain, which were not treated by using a corticosteroid, disappeared and had not recurred after 6 months. Conclusion: These cases indicate that JRT may be effective in treating HSP in patients who demonstrate Yin deficiency, even though the number of cases was limited to five.